2022
DOI: 10.24925/turjaf.v10i8.1486-1490.4629
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutrient Availability in Soil Textural Constituent as Influenced by Land Use

Abstract: Investigating the nutrient composition in soil textural constituent as influenced by land use is a necessity towards a good soil conservative and management measure. In view of this, a laboratory experiment was conducted; soil samples were collected from different locations within and outside the Federal University of Technology, Akure and analyzed for basic chemical elements. The soil sampling was based on land use and six different soil samples were collected at a depth of 0-15cm. These samples included bare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Biochar is highly recalcitrant due to its condensed structure (Spokas et al, 2012) and is derived from the thermal decomposition of biomass in an environment with low or no oxygen at moderately low temperatures. Several studies have shown that biochar can ameliorate soil nutrients status, cation exchange capacity in the soil, soil structure, nutrient use efficiency, waterholding, nutrient-holding capacity, and saturated hydraulic conductivity, while decreasing soil acidity (Lehmann et al, 2006;Asai et al, 2009;Karhu et al, 2011;Akingbola et al, 2021Akingbola et al, , 2022. Increases in yield with biochar application have been reported for crops such as cowpea (Yamato et al, 2006), soybean (Tagoe et al, 2008), maize (Yamato et al, 2006;Rodríguez et al, 2009), upland rice (Asai et al, 2009), paddy rice (Shackley et al, 2011;Sokchea and Preston, 2011) and water spinach (Southavong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Biochar is highly recalcitrant due to its condensed structure (Spokas et al, 2012) and is derived from the thermal decomposition of biomass in an environment with low or no oxygen at moderately low temperatures. Several studies have shown that biochar can ameliorate soil nutrients status, cation exchange capacity in the soil, soil structure, nutrient use efficiency, waterholding, nutrient-holding capacity, and saturated hydraulic conductivity, while decreasing soil acidity (Lehmann et al, 2006;Asai et al, 2009;Karhu et al, 2011;Akingbola et al, 2021Akingbola et al, , 2022. Increases in yield with biochar application have been reported for crops such as cowpea (Yamato et al, 2006), soybean (Tagoe et al, 2008), maize (Yamato et al, 2006;Rodríguez et al, 2009), upland rice (Asai et al, 2009), paddy rice (Shackley et al, 2011;Sokchea and Preston, 2011) and water spinach (Southavong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%